BEST PRACTICES IN TEACHING LISTENING FOR YOUNG LEARNERS - Eva Nikmatul Rabbianty (OKARA: Jurnal Bahasa dan Sastra, 2011)
English as an international language, in Indonesia, formally begins to teach since elementary school. Moreover nowadays, many people realize the importance of learning English as an international language. For, parents try to send their young learners into school that has an English subject in their curriculum or into English courses. Children who learn English at their early age is called young learners. In learning English, the young learners will learn the four language skills at least. They are; listening, speaking, reading and writing. This article is going to discuss about any best practices to teach listening, as the first skill acquired by the young learners, in a language classroom.